Hubungan antara Self-Efficacy dengan Stres Akademik Pada Siswa Kelas XI Di SMAN 4 Pandeglang dan Implikasi dalam Layanan Bimbingan dan Konseling - Aprilia, Julianti (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aims to examine the relationship between self-efficacy and academic stress among eleventh-grade students at SMAN 4 Pandeglang. The research employed a quantitative correlational approach with a sample of 213 students selected through simple random sampling. The instruments used were self-efficacy and academic stress questionnaires, tested for validity ahind reliability. Data analysis using the Product Moment Correlation (Pearson Correlation) revealed a coefficient of r = -0.776, which is higher in absolute value than r table = 0.281, with a significance level of 0.000 < 0.05, indicating a significant negative relationship between self-efficacy and academic stress. This means that the higher the students’ self-efficacy, the lower their academic stress, and vice versa. These findings highlight the importance of guidance and counseling services, particularly group guidance, in enhancing students’ self-efficacy so they can better cope with academic stress.